Addressing the Current Pedagogical Challenges of Architectural Education in Nigeria; a Study of Curriculum Contents and Factors Affecting Physical Learning Environment - Nicholas Obi; FRANCIS OKEKE; Rosemary Nnaemeka-okeke (Universitas Diponegoro, 2022)
The current curriculum design, program and the state of the physical learning environment in the Nigerian schools of architecture seem inadequate and ineffective. The study examined the teaching of architecture in Nigerian tertiary institutions. The aim is to ascertain the state of the present curriculum contents and learning facilities. Major Challenges identified in this study include dearth of learning facilities, inability to reform the curriculum contents and limited financial resources allocation to run the schools. Also increasing unemployment for architecture graduates and unskilled nature of practicing graduates were also included. Highlighted in the discussion for necessary intervention by stakeholders of Nigerian tertiary institutions includes review and upgrading of existing curriculum, efficient time-management skills and collaborative teaching and learning techniques. For physical learning environment, literature points that a clean, bright, organized and open-plan ventilated space strengthens learning by motivation. The result from the survey carried out on physical classroom environment among students of tertiary institutions, indicates that the level of satisfaction was fairly satisfactory and that the students expressed that large halls, large corridors were the most available facilities (63.2% and 52.8% respectively). The major equipment in the classroom were whiteboards (100%), personal computers (47.2%) and digital projector or smart board (30.4%), while the available facilities for pleasant environment were attractive surroundings (100.0%). Adjustment of training methodology, improving training skills, retraining the trained, upgrading infrastructure and facilities; expansion of the curriculum and training program were recommended in order to comply with the current global trends.